(untitled) (The Review of Diabetic Studies, 2025)
In this study we focus on ongoing developments in Saudi Arabia’s health care sector, emphasizing the expansion of privatization and public–private partnerships as key parts of the national health transformation. We aim to examine how health care privatization affects hospital performance indicators, using Abha Maternity and Children Hospital as a case study. A total of 45 participants from various administrative and clinical roles at the hospital took part in this exploratory field study, supported by a descriptive and analytical approach. We collected data through a five-point Likert scale questionnaire. The results show that the hospital’s performance is moderate, with some areas gradually improving. The employees were well-informed about methods to improve service through performance indicators, although the many neutral responses to certain questions suggest there may be inconsistencies in their application. Based on these findings, we recommend more training within the hospital on measuring and utilizing performance as well as improved communication.